Suppression of B-RafV600E melanoma cell survival by targeting mitochondria using triphenyl-phosphonium-conjugated nitroxide or ubiquinone. Issue 2 (1st February 2017) - Hong, Seung-Keun; Starenki, Dmytro; Wu, Pui-Kei; Park, Jong-In
ABSTRACT: Most BRAF -mutated melanomas initially responsive to the FDA-approved inhibitors preferentially targeting B-Raf mutated in Val600 residue eventually relapse, requiring additional therapeutic modalities. Recent studies report the significance of metabolic reprograming in mitochondria for maintenance of BRAF -mutated melanomas and for development of their drug resistance to B-Raf inhibitors, providing a rationale for targeting mitochondria as a potential therapeutic strategy for melanoma. We therefore determined whether mitochondria-targeted metabolism-interfering agents can effectively suppress human B-Raf V600E melanoma cell lines and their dabrafenib/PLX4032-resistant progenies using mitochondria-targeted carboxy-proxyl (Mito-CP) and ubiquinone (Mito-Q). These agents exhibited comparable efficacy to PLX4032 in suppressing SK-MEL28, A375, and RPMI-7951 cells in vitro . As determined in SK-MEL28 and A375 cells, Mito-CP induced apoptotic cell death mediated by mitochondrial membrane depolarization and subsequent oxidative stress, which PLX4032 could not induce. Of note, Mito-CP also effectively suppressed PLX4032-resistant progenies of SK-MEL28 and A375. Moreover, when orally administered, Mito-CP suppressed SK-MEL28 xenografts in mice as effectively as PLX4032 without serious adverse effects. These data demonstrate that mitochondria-targeted agents have therapeutic potential to effectively suppress BRAF –mutated melanomas via an effect(s) distinct from those of B-Raf inhibitors.